Capacitively coupled contactless conductivity detection for analytical techniques – Developments from 2018 to 2020 - Hauser, Peter C.; Kubáň, Pavel (Journal of Chromatography A, 2020)
•Developments and applications of C4D in analytical techniques are reviewed.•The period of the last two years from mid-2018 to mid-2020 is covered.•Instrumental innovations and practical examples of C4D are discussed.•Applications in CE, MCE, IC, LC, flow through and paper-based analytical techniques are presented.•Analyses of food, clinical, environmental, industrial and academic samples are summarized. The developments of analytical contactless conductivity measurements based on capacitive coupling over the two years from mid-2018 to mid-2020 are covered. This mostly concerns applications of the technique in zone electrophoresis employing conventional capillaries and to a lesser extent lab-on-chip devices. However, its use for the detection in several other flow-based analytical methods has also been reported. Detection of bubbles and measurements of flow rates in two-phase flows are also recurring themes. A few new applications in stagnant aqueous samples, e.g. endpoint detection in titrations and measurement on paper-based devices, have been reported. Some variations of the design of the measuring cells and their read-out electronics have also been described.